The middle-income trap - Csáki, György (Studia Mundi – Economica, 2019)
The spectacular development of some emerging economies in East-Asia, including that of China, drew the general attention to the possibilities and difficulties to overcome underdevelopment. Two new narratives emerged in recent years for the explanation of successes and failures: the middle-income trap as a possible explication of difficulties and the developmental state as a variety of capitalism that may lead to success. In this paper we try to introduce the different concepts about the nature and characteristics of the middle-income trap and to elaborate how the developmental state can serve to escape the middle-income trap.
Keywords: development; middle-income trap